Co-Creation with FarMoRe: Collaborative training for agroecological transition - Tran, Nguyen Bao; Dittmer, Kyle M; Cuong, Ong Quoc; Trang, Vu Hong; Nelson, Katherine (2024)
The “Co-Creation with FarMoRe: Collaborative Training for Agroecological Transition” curriculum is designed to empower rice farmers, agricultural field agents, and cooperatives in Vietnam’s Mekong River Delta by integrating agroecological practices with innovative digital tools. As part of the EU-IFAD funded Agroecological TRANSITIONS for Building Resilient and Inclusive Agricultural and Food Systems (TRANSITIONS) program, this curriculum supports the development of inclusive, sustainable agricultural systems that increase resilience to climate change while enhancing food security and farmer livelihoods.